Wheat domestication in light of haplotype analyses of the Brittle rachis 1 genes (BTR1-A and BTR1-B). (August 2019) - Nave, Moran; Avni, Raz; Çakır, Esra; Portnoy, Vitaly; Sela, Hanan; Pourkheirandish, Mohammad; Ozkan, Hakan; Hale, Iago; Komatsuda, Takao; Dvorak, Jan; Distelfeld, Assaf
Highlights: Wheat carry mutations in the BTR1-A and BTR1-B genes affecting spike shattering. We probed the geographical provenances of these mutations via haplotype analyses. The progenitor haplotypes were identified in a collection of wild wheat accessions. A single Southern Levant accession harbored both BTR1 progenitor haplotypes. This imply that Southern Levant played an important role in wheat domestication. Abstract: Wheat domestication was a milestone in the rise of agrarian societies in the Fertile Crescent. As opposed to the freely dispersing seeds of its tetraploid progenitor wild emmer, the hallmark trait of domesticated wheat is intact, harvestable spikes. During domestication, wheat acquired recessive loss-of-function mutations in the Brittle Rachis 1 genes, both in the A genome ( BTR1-A ) and B genome ( BTR1-B ). In this study, we probe the geographical provenances of these mutations via haplotype analyses of a collection of wild and domesticated accessions. Our results show that the precursor of the domesticated haplotype of BTR1-A was detected in 32% of the wild accessions gathered throughout the Levant, from central Israel to central Turkey. In contrast, the precursor of the domesticated haplotype of BTR1-B, which carries a distinct 11 bp deletion in the promoter region, was found in only 10% of the tested wild accessions, all from the Southern Levant. Moreover, we identified of a single wild emmer accession in Southern Levant that carries the progenitor haplotypes for both BTR1-A and BTR1-B genes. These observations suggest that at least part of the emmer domestication process occurred in Southern Levant, contrary to the widely held view that the northern part of the Fertile Crescent was the center of wheat domestication.